2011
DOI: 10.1515/reveh.2011.012
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the molecular mechanisms of nickel-induced genotoxicity and carcinogenicity: a literature review

Abstract: Nickel, a naturally occurring element that exists in various mineral forms, is mainly found in soil and sediment, and its mobilization is influenced by the physicochemical properties of the soil. Industrial sources of nickel include metallurgical processes such as electroplating, alloy production, stainless steel, and nickel-cadmium batteries. Nickel industries, oil- and coal-burning power plants, and trash incinerators have been implicated in its release into the environment. In humans, nickel toxicity is inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
106
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(112 citation statements)
references
References 76 publications
5
106
0
1
Order By: Relevance
“…The Ni-treated animals had bilateral hind leg paralysis and had to be euthanized at Day 2, indicating that a bolus of 20 mg Ni was highly toxic and too high a dose to act as an effective ''positive'' control and model unacceptable long-term biologic effects. Nickel has been shown to be both immunogenic and carcinogenic in humans [4,14]. In animal studies Ni has been shown to compete with Ca(2?)…”
Section: Discussionmentioning
confidence: 99%
“…The Ni-treated animals had bilateral hind leg paralysis and had to be euthanized at Day 2, indicating that a bolus of 20 mg Ni was highly toxic and too high a dose to act as an effective ''positive'' control and model unacceptable long-term biologic effects. Nickel has been shown to be both immunogenic and carcinogenic in humans [4,14]. In animal studies Ni has been shown to compete with Ca(2?)…”
Section: Discussionmentioning
confidence: 99%
“…The maternal nutrition is very important during lactation, and it is at the forefront of priorities in health programs [3]. The components of the breast milk promote infants' protection against infectious diseases, increasing the intelligence quotient (IQ) as well as the emotional and psychological development of the infants [4].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, avoiding foods with Ni reduced body fat and BMI in overweight women allergic to the metal, particularly those in the early menopause stage. Plus, the Ni absorption rate via drinking water is far higher than that of via food [19,29,30]. Since limited information is available about the effect of Ni in drinking water on weight loss or gain, additional studies should seek to determine the relationship between obesity and drinking water nickel levels.…”
Section: Discussionmentioning
confidence: 99%